Assessment of the flexibility of elite athletes using the modified Thomas test - Harvey, D. (British Journal of Sports Medicine, 1998)
AIM: To analyse the modified Thomas test and obtain measures of flexibility for the iliopsoas, quadriceps and tensor fascia lata/iliotibial band. METHOD: The modified Thomas test was used to determine the range of flexibility of 117 elite athletes in tennis, basketball, rowing, and running. RESULTS AND CONCLUSION: The study has provided objective data for a clinical test measuring flexibility of the iliopsoas, quadriceps, and tensor fascia lata/iliotibial band. It is recommended that sufficient flexibility is obtained to perform a specific sport and that asymmetries between limbs are addressed.